The Effectiveness of UK School-Based Mental Health Programs for Neurodivergent Adolescents: A Policy Review of Sen (Special Educational Needs) and Inclusive Education Strategies - Adindu, Kelechi Nelson; Alao, Oluwaseyi Joy; Ige, Temiloluwa; Nwudele, Uchechukwu; Ohanu, Chikezie Frederick; Onakoya, Ademola; Anadu, Judith U.; Awoyemi, Bukola; Chukwunonye, Chisom; Riches, Anointed (British Journal of Healthcare and Medical Research, 2025)
This review aimed to evaluate the effectiveness of UK school-based mental health programs for neurodivergent adolescents by assessing the impact of interventions on well-being, identifying implementation barriers, analyzing policy alignment, and providing recommendations. Utilizing a mixed-method systematic review, the study integrated quantitative data from 18 randomized controlled trials and 12 quasi-experimental studies, alongside qualitative insights from interviews and focus groups. The population consisted of neurodivergent adolescents (ages 11–18) in UK educational settings. Meta-analysis revealed significant improvements in emotional regulation (Hedges’ g ≈ 0.72), anxiety reduction (g ≈ 0.62), depressive symptoms (g ≈ 0.54), and school engagement (g ≈ 0.49). Qualitative findings highlighted increased student self-confidence and coping skills, but also identified stigma, sensory sensitivities, and access challenges. Key implementation barriers included limited funding, inadequate educator training, and regional service disparities. The review concludes that while school-based programs show substantial potential benefits, consistent implementation and specialized staff training are crucial. Policy reforms should prioritize mandatory mental health training for educators, establish dedicated school-based mental health teams, and expand government-funded regional support networks. Longitudinal studies are needed to assess long-term effectiveness and to develop adaptable mental health frameworks for diverse school contexts.